Athletes and coaches through COVID-19 pandemic: a qualitative view of goal management - Costa, S.; De Gregorio, E.; Zurzolo, L.; Santi, G.; Ciofi, E. G.; Di Gruttola, F.; Morgilli, L.; Montesano, C.; Cavallerio, F.; Bertollo, M.; di Fronso, S. (International Journal of Environmental Research and Public Health, 2022)
Since the end of 2019 and throughout 2020 the world has been devastated by the SARS COVID-19 pandemic. The sport world suddenly had to deal with a massive reorganization of events with important implications on the physical and psychological preparation of athletes and coaches. The purpose of this study was to explore how these changes impacted coaches` and athletes` goal setting strategies and their experience of goal adjustment. As part of a wider mixed-method project involving 2162 coaches and 1354 athletes, an online qualitative survey was used, and data collected were analyzed using reflexive thematic analysis. Findings highlighted three overarching themes, in response to goal adjustment: "Moving on toward new goals", "Letting go of goals", and "Trying to hold on", with several themes and sub-themes identifying different nuances of athletes` and coaches` experience. The implications of such findings for the mental preparation of high-level athletes are discussed in two ways. Firstly, in light of existing literature on goal setting from an applied perspective; secondly, in the broader perspective of the sport culture and the application of our themes to other challenging moments that sport professionals might encounter.